Optimizing quinoa growth cycle duration in northeast England by varying the sowing date. (30th July 2022) - Domingos, Israel; Bilsborrow, Paul
Abstract: Quinoa ( Chenopodium quinoa Willd.) is attracting interest as a key contributor to global food and nutritional security. This study evaluated the effects of and interactions between sowing date (mid‐April vs. early May) and variety ('Atlas' and 'Jessie') on the performance of quinoa in northeast England over three seasons (2016–2018). Grain yield was about 1 Mg ha −1 on average across all treatments, associated with poor crop establishment (56.6%) and a prolonged crop growth cycle (165 d). The highest grain yield of 1.70 Mg ha −1 was achieved from the late‐maturing variety Atlas in 2017, which was also supported by the highest harvest index and yield components. Grain yield, protein content, and Zn concentration were all significantly higher for the late sowing, whereas total antioxidant concentration was significantly higher in response to the early sowing date. Grain Zn (43.8 mg kg −1 ), Fe (123.1 mg kg −1 ), and protein (13.4%) concentrations were higher on average than those reported for major cereals with particularly high protein (14.8%) and Zn (63.8 mg kg −1 ) concentrations achieved in 2017. Despite the relatively low yield, varietal differences in crop yield and development can be targeted for future crop improvements to suit the cool temperate climate of northeast England. Core Ideas: The grain yield of quinoa was 0.93 Mg ha −1, averaged across variety, sowing dates, and years. The cool temperate climate of northern England resulted in a long growth cycle (131–191 d). Later sowing of quinoa resulted in a significantly higher grain yield and protein content. Later sowing increased Zn and decreased total antioxidant concentration.